Water chemistry of nuclear reactor systems 3 : proceedings of an international conference organised by the British Nuclear Energy Society and co-sponsored by the Institution of Chemical Engineers and the Royal Society of Chemistry, Bournemouth, 17-21 October, 1983. Vol. 2 (British Nuclear Energy Society, 1984)
Proceedings of third international conference held in Bournemouth on 17-21 October 1984.
Keywords: Water cooled reactors -- Congresses.; Water chemistry -- Congresses.; Nuclear power plants -- Water-supply -- Congresses.; elektronické knihy; electronic books